WHAT MOTIVATES POLITICAL PREFERENCES? SELF-INTEREST, IDEOLOGY, AND FAIRNESS IN A LABORATORY DEMOCRACY. - ESAREY, JUSTIN; SALMON, TIMOTHY C.; BARRILLEAUX, CHARLES (Economic Inquiry, 2012)
Substantial prior literature has established that subjects in laboratory experiments are typically willing to sacrifice their own well being to make financial allocations more equal among participants. We test the applicability of this result in an environment that contains some of the key contextual issues that are usually excluded from more abstract games, but which might be important in situations involving income redistribution. Our general finding is that votes for a redistributive tax are almost entirely in accordance with self-interest: above-average earners vote for low tax rates and below-average earners vote for high tax rates. A measure of subjects' preferences for fairness or equality, their self-reported economic ideology, is not directly related to their voting behavior in this experiment. Because the ideology measure should be correlated with any intrinsic preferences regarding inequality aversion, we conclude that any preferences for fairness or inequality that our subjects possess are not strong enough to overcome self-interest in this context. We do, however, find evidence for a possible indirect effect of ideology on choice behavior in that more conservative subjects tend to be more responsive to their self-interest than the more liberal subjects. ( JEL C90, D63)